2020
DOI: 10.3390/nano10050870
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanoparticles for Therapy and Theranostics of Hepatocellular Carcinoma (HCC) and Liver-Targeting

Abstract: Chitosan nanoparticles are well-known delivery systems widely used as polymeric carriers in the field of nanomedicine. Chitosan is a carbohydrate of natural origin: it is a biodegradable, biocompatible, mucoadhesive, polycationic polymer and it is endowed with penetration enhancer properties. Furthermore, it can be easily derivatized. Hepatocellular carcinoma (HCC) represents a remarkable health problem because current therapies, that include surgery, liver transplantation, trans-arterial embolization, chemoem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 106 publications
1
22
0
Order By: Relevance
“…The mucoadhesive properties of chitosan can increase drug penetration into cancer cells and suppress drug efflux reactions to maximize the level of drug entering the cells. In addition, chitosan nanoparticles can inhibit cell migration activity in MDA-MB-231 [ 15 ], and improve anticancer activities in HeLa [ 16 ], HUVE [ 17 ], and HCC cells [ 18 ]. The activities of chitosan in killing cancer cells are known to work through the mechanism of induction of apoptosis through activation of caspases 3, 8, 9; modulation ratio of Bax: Bcl-2; induce DNA damage [ 19 , 20 ] and the characteristics of chitosan undergo protonation in acidic environments and provide useful release at low pH as in tumor microenvironment that has acidic pH [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mucoadhesive properties of chitosan can increase drug penetration into cancer cells and suppress drug efflux reactions to maximize the level of drug entering the cells. In addition, chitosan nanoparticles can inhibit cell migration activity in MDA-MB-231 [ 15 ], and improve anticancer activities in HeLa [ 16 ], HUVE [ 17 ], and HCC cells [ 18 ]. The activities of chitosan in killing cancer cells are known to work through the mechanism of induction of apoptosis through activation of caspases 3, 8, 9; modulation ratio of Bax: Bcl-2; induce DNA damage [ 19 , 20 ] and the characteristics of chitosan undergo protonation in acidic environments and provide useful release at low pH as in tumor microenvironment that has acidic pH [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review reported the application of chitosan NPs in therapeutics and theranostics of hepatocellular carcinoma (HCC) to overcome the limitations of conventional HCC therapies [ 116 ]. NPs were prepared with specific ligands enabling liver targeting and the results showed improved inhibition of tumor growth combining the benefits of diagnosis at early disease stage along with improved therapeutics.…”
Section: Recent Developments In the Utility Of Chitosan Npsmentioning
confidence: 99%
“…In addition, it owns a lipid-lowering capacity, through promoting weight loss, lowering LDL, and boosting high-density lipoprotein (HDL), with a suggested mechanism linked to the polymer’s positive charge, which attracts the negatively charged fatty acids and bile acids binding them to the indigestible chitosan fiber [ 100 ]. Interestingly, this unique polymer can deliver genes and target the liver [ 101 , 102 , 103 ], which nominates it to be the polymer of choice for smart anti-MAFLD nanomedicine delivery.…”
Section: Opportunities and Limitations Of Nanosystems For Mafld Thmentioning
confidence: 99%